2016
DOI: 10.1175/mwr-d-15-0147.1
|View full text |Cite
|
Sign up to set email alerts
|

Downslope Windstorms of San Diego County. Part I: A Case Study

Abstract: The “Santa Ana” wind is an offshore flow that affects Southern California periodically during the winter half of the year, typically between September and May. The winds can be locally gusty, particularly in the complex terrain of San Diego County, where the winds have characteristics of downslope windstorms. These winds can cause and/or rapidly spread wildfires, the threat of which is particularly acute during the autumn season before the onset of winter rains. San Diego’s largest fires, including the Cedar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 54 publications
3
53
0
Order By: Relevance
“…Despite the massive destruction wrought by the Diablo winds, associated with the Northern California firestorm of October 2017 and the Oakland Hills firestorm of 1991, very little is known quantitatively about them, especially relative to the Southern California downslope winds that favor wildfires, such as Santa Ana [1][2][3][4][5][6][7][8][9][10] and Sundowner [11][12][13][14][15] winds. A prescient preliminary analysis of 'Santa Ana-like' winds in the Oakland Hills was performed in 1973 [16], some 18 years prior to the Oakland Hills fire of 1991, and analyses [17][18][19] subsequent to that fire confirmed their localization at the eastern San Francisco Bay Area.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the massive destruction wrought by the Diablo winds, associated with the Northern California firestorm of October 2017 and the Oakland Hills firestorm of 1991, very little is known quantitatively about them, especially relative to the Southern California downslope winds that favor wildfires, such as Santa Ana [1][2][3][4][5][6][7][8][9][10] and Sundowner [11][12][13][14][15] winds. A prescient preliminary analysis of 'Santa Ana-like' winds in the Oakland Hills was performed in 1973 [16], some 18 years prior to the Oakland Hills fire of 1991, and analyses [17][18][19] subsequent to that fire confirmed their localization at the eastern San Francisco Bay Area.…”
Section: Introductionmentioning
confidence: 99%
“…Southern California windstorm-driven fires are associated with Santa Anas-seasonal pressure-driven offshore flows-and sundowners. Curiously, although the phenomenon has long been recognized (i.e., [27]) simulations of the structure of Santa Anas (e.g., [73]) and Santa Ana-driven fire events (e.g., [17,59]) have been overlooked until recently. Similarly, the Diablo winds of northern California have historically driven some of the most destructive events (e.g., the 1991 Oakland Hills fire and the 2017 Napa and Sonoma County fires) but other than general descriptions of cause and appearance, have not been modeled in fine detail.…”
Section: Specific Scenariosmentioning
confidence: 99%
“…Most notable was the Witch Creek fire in San Diego County, where wind gusts of 26 m s 21 were observed at the Julian weather station along with relative humidity values of '5%. However, high-resolution model simulations at 667 m showed that wind velocities were much higher in unsampled areas (Cao and Fovell 2016). This event became the catalyst for the development of a comprehensive Santa Ana wildfire potential index to better inform fire agencies, first responders, private industry, and the general public about the severity of an approaching event.…”
Section: Introductionmentioning
confidence: 99%
“…Although not frequent, significant fire activity associated with these winds in this zone has occurred in the past, which is why this geographic area is now represented in the index. Santa Ana winds across zones 1 and 2 are primarily a result of offshore surface pressure gradients (locally and/or synoptically) interacting with the local terrain to produce gap winds through the Soledad Canyon, the Cajon Pass, and the Banning Pass Cao and Fovell 2016). These winds also tend to precede the Santa Ana winds that occur across San Diego County by 12-24 h. Across zone 3, offshore winds take on a more ''downslope windstorm'' characteristic driven largely by the tropospheric stability (Cao and Fovell 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation